Incorporation of Sustainable Development Goal 4 in Biology Curriculum Design: A Case Study - Gew, Lai Ti *; Annyza Tumar, * (International Islamic University College Selangor (KUIS), 2023)
Curriculum design needs to be undertaken at both programme and subject level. The programme structure needs to enable the graduates to also acquire integrative biotechnology laboratory skills and employability skills. Module-specific knowledge and skills are essentially important, but they are meaningless on their own. This paper focuses on the review of one subject, i.e. BIO 2134 Instrumental Analysis, with the aim of examining the targets in Sustainable Development Goal (SDG) 4 - particularly Target 4.4 on increasing the number of people with relevant skills for financial success (employability skills), and Target 4.7 on education for sustainable development and global citizenship – and how they can be better achieved. We focused on the learning outcomes (LOs), assessments, and teaching and learning activities. First, we refined the 4 LOs to 3 to reduce overlaps and repetitions, as well as to improve students’ assessment workload. Secondly, we expanded the scope of one of the assessments by including the element of entrepreneurship into the research proposal. The study can provide very useful information for a larger scale review of the curriculum redesign to probe if similar changes can be done for other modules in the programme to be aligned with the SGDs agenda and its action of framework.